Mary Warnock : Ethics, Education and Public Policy in Post-War Britain. - Graham, Philip (Cambridge, UK : Open Book Publishers, 2021)
This biography illuminates the life and thought of Baroness Mary Warnock, whose active years spanned the second half of the twentieth century, a period during which opportunities for middle-class women rapidly and vastly improved.
Intro -- Contents -- Preface -- 1. Changing Times for Women (1950-2000): Two Views from the Top -- 2. Blissful Beginnings -- 3. Emerging -- 4. The Good Life -- 5. Fitting It All In -- 6. What Are Schools For? -- 7. All Change for Special Education -- 8. Infertility -- 9. What Are Universities For? -- 10. Art and Nature -- 11. The Manner of Our Deaths -- List of Figures -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books